2020
DOI: 10.3390/educsci10050138
|View full text |Cite
|
Sign up to set email alerts
|

“Preparing Them for the Road”: African Migrant Parents’ Perceptions of Their Role in Their Children’s Career Decision-Making

Abstract: There are numerous theories on parenting styles, however, they are Western-oriented and may not be applicable to collectivist non-Western societies. A qualitative study which utilised semi-structured interviews was conducted to explore the perceived parenting roles of 26 Sub-Saharan African (SSA) migrant parents (both humanitarian and professional migrants) in their children’s career pathways after they migrated to Australia. Data were analysed using grounded theory methods and this process facilitated the cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Corporal punishment, for instance, may have different meanings in Sub-Sahara African families than that of western families [ 43 ]. For example, Eritrean parents are more authoritarian towards their children and deeply interfere in all aspects of their lives even when they reach adulthood [ 44 ]. Likewise, children grow up in wide social networks of extended families where religious and cultural beliefs play significant roles in the daily lives and well-being of people [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corporal punishment, for instance, may have different meanings in Sub-Sahara African families than that of western families [ 43 ]. For example, Eritrean parents are more authoritarian towards their children and deeply interfere in all aspects of their lives even when they reach adulthood [ 44 ]. Likewise, children grow up in wide social networks of extended families where religious and cultural beliefs play significant roles in the daily lives and well-being of people [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In-depth exploration of the findings revealed that participants' career choices are filtered through the lens of the SSA's acculturation model -prioritizing family needs and societal expectations (Akosah-Twumasi et al, 2020a). These familial and societal expectations serve as restrictive obligations that present a "fork in the career decision-making road" -a dilemma as to which career option to choose.…”
Section: Discussionmentioning
confidence: 99%
“…Family solidarity and commitment are also the normative practice of Chinese families as they maintain filial obligations to provide help to elderly parents (Ofstedal et al, 2004;Thang, 2010;Guo et al, 2012). Whether they live in their home country or they have migrated, families from SSA and Asia tend to maintain their heritage societal practices of familial duty and reciprocal obligations to the community (Sue and Okazaki, 1990;Kao and Thompson, 2003;Zhang, 2004;Akosah-Twumasi et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations